Design and analyzing of small blade wind turbine - Zarina, Amat Jafar (2009)
Renewable energy is now very popular in replacing the power sources that been available in the market. It was a good source which gives a lot of advantages to the environment also to the world community. For this project, the focus is on one of renewable energy that been popular since 19th century. Wind power system before had been a popular used among the farmer and rural country which did not have any electric supplier. The blade wind turbine, play an important role to the wind turbine performance. According to the previous research, it had been stated that the shape of blade wind turbine is the most critical part in wind turbine as it the one that will capture the wind. From the previous research, the pioneer of the small wind turbine already was using an aerodynamics concept in making the shape design for the blade wind turbine. There are several types of aerofoil concept in the market, but the shape that always being used is three popular type that is flat bottom, curved bottom and symmetrical. For this project, the analysis is to find out from these three types of shape which can produce a higher lift force with lower drag force. The analysis was done by using CFD Cosmos Floworks. In CFD, the parameter being search is the Lift and the Drag force. From the analysis result that being review, it was clear that the best shape design that can produce higher lift force with lower drag force is the flat bottom type with 0.03m thickness.